2006
DOI: 10.1007/s10570-005-9023-2
|View full text |Cite
|
Sign up to set email alerts
|

Spiral structures of cotton fiber

Abstract: In the present article, data from the microscopic investigation of the morphological structure of a cellular wall and plasmalemma of the Central Asian cotton fiber are given at different stages of their development. The objects under investigation were live hairs of five middle-fiber cotton species (Tashkent-1, 108-F, Namangan-77, Margelan-3, G. llirsutum L.) and the coarse-fiber variety of G. arboreum L., so-called Turfan Gtiza. To observe the cotton hair surface morphology, the original method of gelatinous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 5 publications
0
14
0
Order By: Relevance
“…It has been observed that, in addition to cutin, pectin, proteins and other components, there is also a large amount of cellulose on the surface layer of cotton fiber (23). Thus, it is tempting to hypothesize that if the enzyme can be engineered to specifically bind to cellulose through a "gain of function" modification, its concentration on the surface of cotton fiber could increase significantly.…”
mentioning
confidence: 99%
“…It has been observed that, in addition to cutin, pectin, proteins and other components, there is also a large amount of cellulose on the surface layer of cotton fiber (23). Thus, it is tempting to hypothesize that if the enzyme can be engineered to specifically bind to cellulose through a "gain of function" modification, its concentration on the surface of cotton fiber could increase significantly.…”
mentioning
confidence: 99%
“…Namely our observing of row of associates of TC reorientation during cellulose deposition let us to establish fact about rotation of plasmamembrane. The direct proof of plasmamembrane rotation we can see from spiral structure of plasmamembrane (Krakhmalev and Paiziev 2006). Especially actively this process take place on the apical point of cotton hair (Figure 1c).…”
Section: Resultsmentioning
confidence: 69%
“…Ordinary biological optical microscopy cannot provide to see in-vivo movement the plasmamembrane too because cotton fiber is not transparent for visible light. The offered in present new method replica-reprint and reflected light microscopy let us see not plasmamembrane, but result its pressing to gelatin (Krakhmalev and Paiziev 2006;Krakhmalev and Zakirov 2000). It is not direct method to see dynamical process but we can do clear conclusions from series of instantaneous images of apical part of cotton cell and plasmamembrane at difference growth stage of cotton (from 1 DPA up to full ripening, see Figures 1 -3).…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…The fibers consist of primary cell wall, cuticle area, secondary cell wall, and lumen area Polymerization occurs at the primary cell wall, cuticle area, and secondary cell wall. Furthermore, cotton cell‐hairs and spiral structures were observed on the surface of the primary cell wall . Such morphologies may produce chiral π‐stacking or macromolecular spiral structure of the resultant PANI layer on the cotton during transcription.…”
Section: Resultsmentioning
confidence: 99%